The new economic sociology : a reader - Dobbin, Frank (Princeton University Press, 2004)
Dobbin presents twenty classic, representative articles in the field of economic sociology and organizes them according to four themes. He thus introduces the field and its history to students and establishes a schema for interpreting the field based on what it hopes to achieve.